Understanding Employees’ Perceptions of Human Resource Practices: Effects of Demographic Dissimilarity to Managers and Coworkers - Jiang, Kaifeng; Hu, Jia; Liu, Songbo; Lepak, David P. (Human Resource Management, 2017)
Strategic HRM researchers have increasingly adopted an employee perspective to understand the influence of HR practices on employee outcomes and have called for studies to explain variability in employees’ perceptions of HR practices. To address this research need, we used the social information processing perspective to examine the contextual influence of managers and coworkers on employees’ perceptions of HR practices and explore demographic dissimilarities as boundary conditions of the contextual influence. Conducting research in two organizational settings, we found that both manager-perceived and coworker-perceived HR practices were positively related to employees’ perceptions of HR practices. The results also revealed that employee demographic dissimilarity to coworkers in terms of age and organizational tenure weakened the positive relationship between coworker-perceived and employee-perceived HR practices. However, the relationship between manager-perceived and employee-perceived HR practices was not influenced by demographic dissimilarities. © 2015 Wiley Periodicals, Inc.